The Impact of Learning Organizations on Organizational Resilience Through Institutionalization: A Study During the Period of Covid-19 - Kaçmaz, Yaşar Yiğit; Çevirgen, Aydın (International Journal of Contemporary Economics and Administrative Sciences, 2021)
This study aims to determine the impact of learning organizations on organizational resilience through institutionalization. The population consisted of the managers of four and five-star accommodation businesses in Alanya, Turkey. The implementation step was conducted during the COVID-19 pandemic in September 2020 in 54 facilities, 43 of which were five-star and 11 four-star. A total of 392 questionnaires were collected while performing the study. As a result of the factor analyses regarding the variables in this study, it was found that organizational resilience consisted of one factor which was also called organizational resilience, that institutionalization included three factors named professionalization-consistency, social responsibility, and formalization, and that learning organization contained two factors called individual and organizational learning. Correlation analyses indicated a positive and significant relationship between the factors of organizational resilience, institutionalization, and learning organization. Hierarchical regression analysis and the Sobel test were utilized to determine the mediating impact. The results of the hierarchical regression analysis indicated that three institutionalization factors had a fully mediating role in terms of the impact of learning organization factors on organizational resilience. Keywords: Organizational Resilience, Institutionalization, Learning Organization, Accommodation Businesses JEL Codes: M19, L20, L29, L83